Estimating Return on Investment (ROI) for a Behavior Change: An Evaluation Tool for Extension Programs - Amanda D. Ali; Laura A. Warner; Hayk Khachatryan (EDIS)
Extension professionals can benefit from knowing the value of a program’s outcomes compared to how much it costs. One way to estimate a program’s value relative to cost is through a series of calculations, known as Return on Investment (ROI). This 4-page fact sheet describes ROI and how Extension professionals can use it in their programming. Written by Amanda D. Ali, Laura A. Warner, and Hayk Khachatryan, and published by the Department of Agricultural Education and Communication, December 2016.